Limestone aggregate purification as a part of the crushing and sieving at the "Kaona" quarry - Miljković Nikola; Stojičić Ivan; Živanović Miloš; Jovanović Nikola; Stefanović Jelena (Mining and Metallurgy Engineering Bor)
As a part of the Main Mining Design for limestone processing at the Open Pit Kaona - Kučevo, a new Crushing Plant has been designed. This paper includes a part of technological process for additional cleaning of limestone with a fraction of -20+0 mm before the primary crushing.